Visits with Lincoln : abolitionists meet the president at the White House - White, Barbara A., 1942- (Lexington Books, 2011)
Visits with Lincoln provides a balanced and readable discussion of ten abolitionists, male and female, black and white, who visited President Lincoln in the White House during the Civil War in an attempt to advance their goal of ending slavery immediately. The book paints a portrait of Lincoln through the eyes of his visitors and traces changes in his ideas and attitudes over the course of the war. The visitors include Jessie Benton Fremont, wife of Major General John Charles Fremont, the famous explorer and commander of the Union army's Department of the West; Harriet Beecher Stowe, Isabella ...